Challenges in genomic analysis of model systems and primary tumors of pancreatic ductal adenocarcinoma - Hyun, Sangyeop; Park, Daechan (Computational and Structural Biotechnology Journal, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by aggressive tumor behavior and poor prognosis. Recent next-generation sequencing (NGS)-based genomic studies have provided novel treatment modes for pancreatic cancer via the identification of cancer driver variants and molecular subtypes in PDAC. Genome-wide approaches have been extended to model systems such as patient-derived xenografts (PDXs), organoids, and cell lines for pre-clinical purposes. However, the genomic characteristics vary in the model systems, which is mainly attributed to the clonal evolution of cancer cells during their construction and culture. Moreover, fundamental limitations such as low tumor cellularity and the complex tumor microenvironment of PDAC hinder the confirmation of genomic features in the primary tumor and model systems. The occurrence of these phenomena and their associated complexities may lead to false insights into the understanding of mechanisms and dynamics in tumor tissues of patients. In this review, we describe various model systems and discuss differences in the results based on genomics and transcriptomics between primary tumors and model systems. Finally, we introduce practical strategies to improve the accuracy of genomic analysis of primary tissues and model systems.
Keywords: Cancer genomics; Clonal evolution; Ductal adenocarcinomas; Genomic studies; Genomics; Genomics analysis; Modelling systems; Next-generation sequencing; Pancreatic ductal adenocarcinoma; Tumor microenvironments; Bioinformatics; Cancer genomics; Clonal evolution; Model system; Pancreatic ductal adenocarcinoma; Tumor microenvironment